An Analysis of Verbal and Visual Sign Found on Grave of The Fireflies Posters - Maria Alvita Nai Modok; I Dewa Ayu Devi Maharani Santika; Desak Putu Eka Pratiwi (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
Abstract The aims of this research are to analyse the meaning of verbal and visual signs found in the poster of Grave of The Fireflies. The data of this research were downloaded from the internet. The semiotic theory by Saussure (1983) was used to analyse the verbal and visual sign while the theory of meaning by Barthes (1977) is applies to explain the meaning of verbal and visual sign in the poster. Besides Saussure and Barthes theory, a supporting theory from Wierzbicka (1996) regarding colours was also applied. The data of this research were analysed by using descriptive qualitative method and the result of this research reveal that 3 verbal signs and 5 visual signs were found in Grave of The Fireflies’ poster. These signs contain both denotative and connotative meanings. In which the denotative meaning reveals the literal meaning of the signs and the connotative meaning reveal more explicit meaning about the film such as the theme, the storyline and the character of the film. Keywords: verbal sign, visual sign, film, poster, Grave of The Fireflies